Future Directions in the Treatment of Gastrointestinal and Pancreatic Neuroendocrine Tumors. Issue 6 (July 2016) - Asmis, Timothy
Abstract : Abstract: Recently, the landscape of the diagnosis and treatment of patients with well-differentiated gastrointestinal/pancreatic neuroendocrine tumors (previously referred to as carcinoid tumors) has changed dramatically. We will need to work with all of the stakeholders including clinicians, patients, regulatory agencies, and industry to best navigate future treatment and research. Future protocols will require us to define clinically relevant end points. In designing future clinical trials, we will need to determine which patients will be included in these studies. Future research will need to address the best way to image and follow patient's disease both in the clinic and on research studies. Timely access to new therapies will be the utmost importance to both current and future patients. We must work together to establish relevant clinical questions and to pursue collaborative research that promotes the health of our patients.